EFFORT TO UTILIZE Nata de Coco AS BULLET-PROOF MATERIAL - , Alfinda Novi Kristanti , Nanik Siti Aaminah , Siti Wafiroh , Di ([Yogyakarta] : Chemistry Departement Universitas Gadjah Mada, 2010)
The most common material used as anti-bullet today is a synthetic polymer Kevlar, which is very expensive and not degradable. The purpose of this study was to obtain an anti-bullets material from domestic raw materials, nata de coco. The expected material obtained will be light and biodegradable. Research was conducted by a team of researchers from the Department of Chemistry, Faculty of Science and Technology, Airlangga University in cooperation with PT. Tropica Nucifera Industry as producers of nata de coco, and researchers from the Research and Development Unit of Defense Department Indonesia. In this research, nata de coco was combined with jute fiber. This combination required the adhesive material which can paste these two fibres, flexible, resistant to water and oil. There were six variations of composition of nata de coco and jute fiber. Mechanical test of these samples showed that the variation 3 had the highest tensile strength. While the highest strain or elongation break was shown by variation 6. Generally, a good bullet proof material has high tensile strength and strain. However, ballistic tests conducted on six variations did not show satisfactory results. Combined all of six variations only stop a bullet from pistol FN 9 mm ammunition caliber 46 and the bullet was deep restrained in the sixth layer.